2022
DOI: 10.1038/s41423-022-00843-8
|View full text |Cite
|
Sign up to set email alerts
|

Avian influenza viruses suppress innate immunity by inducing trans-transcriptional readthrough via SSU72

Abstract: Innate immunity plays critical antiviral roles. The highly virulent avian influenza viruses (AIVs) H5N1, H7N9, and H5N6 can better escape host innate immune responses than the less virulent seasonal H1N1 virus. Here, we report a mechanism by which transcriptional readthrough (TRT)-mediated suppression of innate immunity occurs post AIV infection. By using cell lines, mouse lungs, and patient PBMCs, we showed that genes on the complementary strand (“trans” genes) influenced by TRT were involved in the disruptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Compared with less virulent seasonal IAV, highly pathogenic avian influenza virus (HPAIV) H5N1, H5N6, and H7N9 can better bypass the innate immune response. Furthermore, through the molecular mechanism of the NS1-SSU72-trans-transcriptional readthrough (TRT)-STAT1/2 axis, AIV infection can reduce the expression of SSU72 and induce TRT, thereby weakening the innate immune response ( Figure 2B ) ( Zhao et al, 2022 ). Thus, restoring SSU72 expression could be a potential strategy for preventing AIV pandemics.…”
Section: Iav Escapes From Innate Immunementioning
confidence: 99%
“…Compared with less virulent seasonal IAV, highly pathogenic avian influenza virus (HPAIV) H5N1, H5N6, and H7N9 can better bypass the innate immune response. Furthermore, through the molecular mechanism of the NS1-SSU72-trans-transcriptional readthrough (TRT)-STAT1/2 axis, AIV infection can reduce the expression of SSU72 and induce TRT, thereby weakening the innate immune response ( Figure 2B ) ( Zhao et al, 2022 ). Thus, restoring SSU72 expression could be a potential strategy for preventing AIV pandemics.…”
Section: Iav Escapes From Innate Immunementioning
confidence: 99%
“…Yan Zhao et al have reported a novel mechanism employed by highly pathogenic avian IAV to further escape host innate immunity, which is through altering the transcriptional readthrough (TRT) [110]. The authors showed that NS1 binds to SSU72 (RNA polymerase II subunit A C-terminal domain phosphatase), leading to a reduction in its expression that eventually induces TRT and represses STAT1/2 mRNA expression, which enabled the virus to evade host antiviral immune responses [110]. IAV infection was also shown to induce the degradation of a sub-nuclear structure known as the Nuclear Domain-10 (ND-10) [111], which has been known to play a role in antiviral defense during IAV infection [112,113].…”
Section: Viral Ns1mentioning
confidence: 99%
“…On the other hand, the SSU72 overexpression reduced lung damage and protected animals infected with H5N1 from inhibiting the antiviral gene expression. Hence, it was emphasized that SSU72 might act as a possible therapeutic target in the treatment of AIV infections [ 186 ].…”
Section: Immune Response To Avian Influenza Virusesmentioning
confidence: 99%